Grants, Concessions, and Original Constitutions of the Province of New Jersey The Acts 289-90, ch. 9 An Act Against Wearing Swords, &c. (2d ed. 1881) - (:unkn) unknown (General Publisher, 1686)
Prohibited the carrying “privately” of any pocket pistol, skeines, stilettoes, daggers or dirks, or other unusual or unlawful weapons by planters. Punishable by fine of five pounds for first conviction, and punishable by imprisonment for six months and a fine of ten pounds.
--
Keywords: CARRY - CONCEALED